Exploratory study of factors associated with adverse clinical features in patients presenting with non-fatal drug overdose/self-poisoning to the ambulance service. Issue 10 (15th September 2010) - Gwini, Stella May; Shaw, Deborah; Iqbal, Mohammad; Spaight, Anne; Siriwardena, Aloysius Niroshan
Abstract : Aim: To investigate the factors associated with adverse clinical features presented by drug overdose/self-poisoning patients and the treatments provided. Methods: Historical patient records collected over 3 months from ambulance crews attending non-fatal overdoses/self-poisoning incidents were reviewed. Logistic regression was used to investigate predictors of adverse clinical features (reduced consciousness, obstructed airway, hypotension or bradycardia, hypoglycaemia) and treatment. Results: Of 22 728 calls attended to over 3 months, 585 (rate 26/1000 calls) were classified as overdose or self-poisoning. In the 585 patients identified, paracetamol-containing drugs were most commonly involved (31.5%). At least one adverse clinical feature occurred in 103 (17.7%) patients, with higher odds in men and opiate overdose or illegal drugs. Older patients and patients with reduced consciousness were more likely to receive oxygen. The latter also had a greater chance of receiving saline. Conclusion: Non-fatal overdose/self-poisoning accounted for 2.6% of patients attended by an ambulance. Gender, illegal drugs or opiates were important predictors of adverse clinical features. The treatments most often provided to patients were oxygen and saline.